2022
DOI: 10.1039/d2sc01180h
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring a robust Al-MOF for trapping C2H6 and C2H2 towards efficient C2H4 purification from quaternary mixtures

Abstract: Light hydrocarbon separation is considered one of the most industrially challenging and desired chemical separation processes and is highly essential in polymer and chemical industries. Among them, separating ethylene (C2H4)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Therefore, Ce-MOF-1 has the potential to separate binary C 2 H 2 /C 2 H 4 and C 2 H 2 /CO 2 mixtures. Nevertheless, Ce-MOF-2 may exhibit unusual C 2 H 6 /C 2 H 4 separation, which is contrary to most C 2 H 4 -selective adsorbents and benefits C 2 H 4 purification in one step. …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Ce-MOF-1 has the potential to separate binary C 2 H 2 /C 2 H 4 and C 2 H 2 /CO 2 mixtures. Nevertheless, Ce-MOF-2 may exhibit unusual C 2 H 6 /C 2 H 4 separation, which is contrary to most C 2 H 4 -selective adsorbents and benefits C 2 H 4 purification in one step. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Emerging as a new class of porous materials, metal–organic frameworks (MOFs) have witnessed great success in the last two decades toward gas storage, separation, catalysis, etc. Remarkably, reticular chemistry , of MOFs has played important roles in the binary separation of C 2 H 2 /C 2 H 4 and C 2 H 4 /C 2 H 6 by virtue of isoreticular and/or isostructural extension/contraction/expansion/functionalization approaches. Very recently, a few groups have even reported that a single MOF material is capable of simultaneous removal of both C 2 H 2 and C 2 H 6 from a ternary mixture of C 2 H 2 /C 2 H 4 /C 2 H 6 to enable C 2 H 4 purification by a single-step process. Additionally, Zaworotko and Chen et al employed the synergistic sorbent separation technique to pack three task-specific MOFs in a fixed-bed column to empower high-purity C 2 H 4 production from the aforementioned ternary mixture …”
Section: Introductionmentioning
confidence: 99%
“…24−28 In particular, the separations of C 2 H 2 from more challenging ternary gas mixtures to model complex C 2 H 2 -rich industrial gas mixtures have rarely been reported. 29,30 To achieve this goal, it is still desirable to explore new MOFs with excellent C 2 H 2 selectivity and high adsorption capacity over other gases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The emerging metal–organic frameworks (MOFs) based on physical adsorption are promising sorbents for gas separation because of their potent predictability and tunability on pore shape/size and functionality. The typical features provide prospective design of target materials with desirable properties for specific molecular recognition. , In this respect, a large number of MOFs were reported to selectively capture C 2 H 2 from CO 2 or other C 1 /C 2 light hydrocarbons. However, for the two important separations of C 2 H 2 from CO 2 or C 2 H 4 , only a few MOFs were found to be effective in the actual breakthrough experiments due to their low selectivity stemming from comparable molecular sizes and physical properties (Table S1). In particular, the separations of C 2 H 2 from more challenging ternary gas mixtures to model complex C 2 H 2 -rich industrial gas mixtures have rarely been reported. , To achieve this goal, it is still desirable to explore new MOFs with excellent C 2 H 2 selectivity and high adsorption capacity over other gases.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum-based MOFs (Al-MOFs) have been reported to show chemical and thermal stability, enabling their application potential, including crystalline sponge, water vapor capture, gas separation and storage. [31][32][33][34][35] In addition, aluminum salts with low price and low toxicity are recognized as ideal industrial catalysts. 36 Although Al-MOFs have been reported frequently, such as MIL-53 (Al), 37 CAU-10, 38 MOF-303, 33 and MOF-520, 39 only a few of them have been utilized as catalysts for CO 2 conversion reactions.…”
Section: Introductionmentioning
confidence: 99%